Abu Ala El-Ma'arri's Opinion on Rajaz | موقف أبي العلاء المعري من الرجز - Ali Hasan Bahar (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2009)
Abu I Ala El-Ma ·arri (449 H/1057 M) was an important figure in the language, literature and criticism. The paper discusses El-Ma ·arri's opinion on the Bahar Rajaz from both two levels; theory and practice. The write also believes that although some researchers have written on El-Ma ·arri but there were no studies on this particular topic.